PENGARUHPUPUK HIJAU AZOLLA (Azolla pinnata) DAN PUPUK NPK TERHADAP PETUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata sturt.) - Afif, Muhammad Naufal; Ariani, Erlida; Dini, Isna Rahma (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims to study the effect of the interaction of azolla green fertilizer and NPK fertilizer on the growth and yield of sweet cornand get the best treatment combination. This research was conducted in experimental garden of Agriculture Faculty of Universitas Riau Bina Widya campus km 12,5 Simpang Baru, Kecamatan Tampan, Pekanbaru. Conducted from March to June 2017. This research uses Factorial Random Design (RAL) which consists of 2 factors. The first factor is the dose of Azolla pinnata green fertilizer consisting of 4 levels: 0 ton/ha, 1,5 ton/ha, 3 ton/ha, and 4,5 ton/ha. The second factor is NPK fertilizer consisting of 4 levels: 0 kg/ha, 75 kg/ha, 150 kg/ha, 225 kg/ha. The parameters observed were relative growth rate, height of plant, number of leaves, time of male flower, time of female flower, age of harvest, weight of cobs weighing per plot, weight of cobs without weight per plot, length of cob, and number of rows. The data obtained were analyzed statistically with vocabulary and continued by Duncan's multiple-range test at 5%. The results showed that the interaction of Azolla pinnatagreen fertilizer and NPK significantly affected the relative growth rate and height of plant, and the effect was not significant on the number of leaves, time of male flower, time of female flower, age of harvest, weight of cobs crawledweighing perplot, weight of the cobs without weightper plot, length of cob and the number of raws. Azolla pinnata green fertilizer 3 ton/ha and NPKfertilizer 150 kg/ha is the best combination on growth and yield of sweet corn.Â Keywords: Azolla pinnata, NPK fertilizer, sweet corn